2021
DOI: 10.1002/brb3.2160
|View full text |Cite
|
Sign up to set email alerts
|

Atrial cardiopathy in embolic stroke of undetermined source

Abstract: The term embolic stroke of undetermined source (ESUS) was introduced in 2014 (Hart et al., 2014); this condition accounts for 17% of all ischemic strokes and has a considerable rate of stroke recurrence of 4%-5%/year (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 50 publications
0
12
2
1
Order By: Relevance
“…The prevalence of NT-proBNP was reported in ESUS vs NCE patients in only one study [27]. Using an NT-proBNP threshold of 250 pg/ml to define AC there was no difference in the prevalence of ESUS and NCE patients with NT-proBNP values above that level after adjusting for potential confounders (OR= 0.73, 95%CI: 0.39-1.35) [28].…”
Section: Serum Biomarkers Of Acmentioning
confidence: 95%
See 2 more Smart Citations
“…The prevalence of NT-proBNP was reported in ESUS vs NCE patients in only one study [27]. Using an NT-proBNP threshold of 250 pg/ml to define AC there was no difference in the prevalence of ESUS and NCE patients with NT-proBNP values above that level after adjusting for potential confounders (OR= 0.73, 95%CI: 0.39-1.35) [28].…”
Section: Serum Biomarkers Of Acmentioning
confidence: 95%
“…Only one study reported the different prevalence of severe LAE among ESUS, NCE and CE stroke patients while another compared its prevalence between ESUS and NCE [20,27]. Specifically, both studies reported an increase in the prevalence of severe LAE in ESUS compared to NCE patients but only one provided significant results (OR=3.41, 95%CI: 1.35-8.61).…”
Section: Echocardiographic Markers Of Acmentioning
confidence: 98%
See 1 more Smart Citation
“…115 Elevated NT-proBNP is a predictor of LA fibrosis and has been used as one of the diagnostic criteria of ACM in some studies. [15][16][17]116 However, a recent study defining ACM as LA enlargement (diameter ≥ 47 mm) or NT-proBNP > 250 pg/ mL indicated a significant difference in the proportion of severe LA enlargement (5.3% vs. 1.4%) rather than elevated NT-proBNP (32.7% vs. 32.3%) between ESUS patients and non-cardioembolic patients, 16 which may be attributed to the fact that NT-proBNP was elevated in the acute stage of ischaemic stroke and thus cannot truly represent ACM. 117 The atrial natriuretic peptide (ANP) is secreted predominantly by the atria, which could more accurately identify ACM than BNP and NT-proBNP in theory.…”
Section: Serum Biomarkersmentioning
confidence: 99%
“…Не исключено, что клиническая и радиологическая картина ИИ на фоне ПК отличается от таковой при «классическом» кардиоэмболическом инсульте в силу различий тромбогенного потенциала ЛП и, следовательно, эмболического материала. В подтверждение этой гипотезы в исследовании J. Chen et al 2021 г. пациенты с инсультом на фоне ПК имели меньшую тяжесть инсульта (1 против 4 баллов по NIHSS) и редкую частоту геморрагической трансформации (0 против 13%) по сравнению с ФП-ассоциированными ИИ [17]. В РКИ CRYSTAL AF не выявлено взаимосвязи между паттерном острого инфаркта мозга и вероятностью обнаружения ФП при инвазивном кардио мониторинге (ИКМ) [18].…”
Section: клинические и радиологические маркеры кардиоэмболииunclassified